Writing at Portuguese Universities: Students’ Perceptions and Practices - Barbeiro, Luís Filipe; Pereira, Luísa Álvares; Carvalho, José Brandão (Journal of Academic Writing, 2015)
In Portuguese higher education, teachers from different scientific areas recognize that their students have difficulties with writing. Nevertheless, preparing students for academic writing is not a priority and any intervention depends more on the interest of particular teachers than on any institutional policy. The development of a more institutional approach to academic writing in Portugal will imply a deeper knowledge of the multifaceted reality of the students’ situation, involving identification of their own perceptions of their writing processes and of the academic writing practices they are subject to. This is the aim of our study, based on 1150 students’ answers to a questionnaire about literacy practices in Portuguese higher education. Our results show that students seem to be conscious of the procedural nature of writing and of the role and importance of planning, composing and reviewing in the course of their writing processes. As for their perceptions about institutional interventions aimed at fostering writing abilities and teacher feedback on their written work, the answers to the questionnaire allow us to conclude that such support is not frequently offered. There are, however, some differences in the way these issues are considered across the various fields of study.